2020
DOI: 10.21608/zumj.2020.29552.1843
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of renovascular hypertension

Abstract: Background: Renovascular hypertension is the commonest form of secondary hypertension. It occurs in less than 5 % of all hypertensive population. There are two forms of renovascular hypertension: Atherosclerotic and fibromuscular dysplasia. Renovascular hypertension is suspected when it develops suddenly in patients under 30 or over 55 years of age, or abruptly worsen in any patient. The aim was to evaluate the indications of surgical treatment of "renovascular hypertension". Methods: Twenty cases with renovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Abdel-Samee [15] confirmed that exposure of farm animals to heat stress in accompanied by a decrease in cholesterol concentration. However, Salem [16] reported that serum cholesterol concentration was significantly higher during summer than in winter. The decline in cholesterol concentration during exposure to heat stress may be due to the increase in total body water or to the decrease in acetate concentration which is the main precursor for the synthesis of cholesterol [17,18].…”
Section: Resultsmentioning
confidence: 97%
“…Abdel-Samee [15] confirmed that exposure of farm animals to heat stress in accompanied by a decrease in cholesterol concentration. However, Salem [16] reported that serum cholesterol concentration was significantly higher during summer than in winter. The decline in cholesterol concentration during exposure to heat stress may be due to the increase in total body water or to the decrease in acetate concentration which is the main precursor for the synthesis of cholesterol [17,18].…”
Section: Resultsmentioning
confidence: 97%